International human rights and mental disability law : when the silenced are heard - Perlin, Michael L., 1946- (New York ; Oxford : Oxford University Press, 2011)
Examining the mistreatment of persons with mental disabilities around the world, Michael Perlin identifies universal factors that contaminate mental disability law, including lack of comprehensive legislation and of independent counsel; inadequate care; poor or nonexistent community programming; and inhumane forensic systems.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Mental health laws; People with mental disabilities -- Civil rights; Insanity (Law)